Structural Evolution of Atomically Thin 1T'‐MoTe2 Alloyed in Chalcogen Atmosphere. Issue 9 (22nd June 2022) - Xu, Tao; Li, Shouheng; Li, Aolin; Yu, Yue; Zhang, Hui; Hu, Ping; Zhou, Wenzhe; Sheng, Liping; Jiang, Tian; Cheng, Haifeng; Cheng, Xiang'ai; Ouyang, Fangping; et al.
Abstract : Alloying is widely applied to tailor properties of 2D materials. Herein, a space‐confined chemical vapor deposition (CVD) strategy to homogeneously grow 100 μm‐sized monolayer 1T'‐MoTe2 in batches is developed. Aberration‐corrected annular dark‐field scanning transmission electron microscopy combined with density functional theory calculations is applied to investigate the atomic structural alteration of 1T'‐MoTe2 alloyed with sulfur. 1T'‐to‐2H phase transition is observed, triggered by both thermodynamic (stability improvement) and kinetic (phase transition barrier reduction) reasons. The alloying degrees of MoS2 x Te2(1− x ) grown at different temperatures display homophilic and random configurations, respectively, providing a feasible approach to tailor the atomic mixture of the alloying elements. The intralayer reconstruction and the interlayer displacement take place as defect concentration increases at elevated alloying temperatures. In contrast, 1T'‐MoTe2 displays high susceptibility in the presence of oxygen. An encapsulation method is developed using CVD‐grown monolayer MoS2, extending the lifetime of monolayer tellurides from several minutes to at least 24 h. These results gain fundamental insights into the structural change in both the beneficial (sulfurization) and detrimental (oxidation) alloying processes of atomically thin 1T'‐MoTe2 and provide a new degree of freedom for the controllable growth of 2D alloys (i.e., tailoring the alloying degree). Abstract : A joint experiment–theory investigation is conducted to unveil the structural evolution of atomically thin 1T'‐MoTe2 after alloying with chalcogen elements down to single‐atom level. Homophilic and random alloy configurations are generated in monolayer MoS2 x Te2(1− x ) at different alloying temperatures, which give fundamental insights into tailoring the atomic mixture of the alloying elements.